2016
DOI: 10.3329/bjas.v45i1.27489
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization and productive potentialities of indigenous dwarf chicken of Bangladesh

Abstract: The study was conducted to investigate the phenotypic features, morphometry and production potentialities of indigenous dwarf chicken (IDC) of Bangladesh under intensive management condition. A total of 48 females and 12 males were collected from different districts and the experiment was performed at BAU Poultry farm for a period of 75 weeks. The predominant plumage and skin color were black and white, respectively. The average shank length, shank circumference and live weight (28 weeks) in adult males and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 12 publications
4
6
2
Order By: Relevance
“…A slightly higher weight at 4 th weeks of age in hilly chicken reported by Rahman et al (2013b) was attributed to a high protein energy diet supplement. While considering body weight by sex and for both sexes combined, H♂ × F♀ crosses in the present study showed a higher body weight at 8 weeks of age compared to other native and improved native chicken genotypes (Faruque et al, 2013;Rahman et al, 2013a;Faruque et al, 2015 andFerdaus et al, 2016). The average body weight at 12 weeks of H♂ × F♀ crosses in this study coincides with the observed body weight for Hilly and desi chickens by Faruque et al (2017).…”
Section: Performance Of Hilly♂ × Fayoumi♀ Crossbred Chickens 321 Bsupporting
confidence: 82%
See 4 more Smart Citations
“…A slightly higher weight at 4 th weeks of age in hilly chicken reported by Rahman et al (2013b) was attributed to a high protein energy diet supplement. While considering body weight by sex and for both sexes combined, H♂ × F♀ crosses in the present study showed a higher body weight at 8 weeks of age compared to other native and improved native chicken genotypes (Faruque et al, 2013;Rahman et al, 2013a;Faruque et al, 2015 andFerdaus et al, 2016). The average body weight at 12 weeks of H♂ × F♀ crosses in this study coincides with the observed body weight for Hilly and desi chickens by Faruque et al (2017).…”
Section: Performance Of Hilly♂ × Fayoumi♀ Crossbred Chickens 321 Bsupporting
confidence: 82%
“…H♂ × F♀ crosses also showed a heavier body weight at 16 weeks in comparison with the average body weight for improved indigenous chicken genotypes recorded by Faruque et al (2015). Ferdaus et al (2016) found 1212 and 1764 gm live weight of female and male indigenous chicken, respectively at 20 weeks of age which is much lower than the present study at the same age. The mean body weights of male birds were significantly heavier (p<0.001) than their female counterpart at hatch and from 4 to 20 weeks of age.…”
Section: Performance Of Hilly♂ × Fayoumi♀ Crossbred Chickens 321 Bcontrasting
confidence: 81%
See 3 more Smart Citations